Stress triggering of the 2022 Lushan–Maerkang earthquake sequence by historical events and its implication for fault stress evolution in eastern Tibet - Tang, Dawei; Ge, Weipeng; Cao, Xiyu (Frontiers in Earth Science, 2023)
It remains unknown how stress triggering causes earthquakes in the eastern Tibetan Plateau following the Wenchuan Earthquake in 2008. The MS 6.1 Lushan earthquake on 1 June 2022 in a seismic gap between the 2008 MW 7.9 Wenchuan earthquake and the 2013 MW 6.6 Lushan earthquake provided an opportunity to detect stress evolution and seismic activity on the fault in this study. We calculated the Coulomb stress change of the June 2022 Lushan–Maerkang earthquake sequence using a Burgers viscoelastic model and, herein, discuss how the sequence have been triggered by historical earthquakes since 1900 in the eastern Tibetan Plateau. Our results suggest the following trends: 1) the 1955 M 7.6 Kangding and 2008 MW 7.9 Wenchuan earthquakes contributed most significant loading effects on the 2022 MS 6.1 Lushan earthquake; however, the 2013 MW 6.6 Lushan earthquake had an unloading effect on the 2022 Lushan earthquake. 2) The 2021 MW 7.3 Maduo earthquake contributed a loading effect on the 2022 Lushan earthquake, and the 2022 Lushan earthquake may have triggered the subsequent Maerkang earthquake swarm on 10 June 2022. 3) Viscoelastic relaxation of the lower crust and upper mantle contributed significantly to fault stress level, while a fault in a late-phase earthquake cycle may have ruptured via slight stress perturbation near a cross-border conversion between positive and negative stress from a far-field earthquake. We also provide a seismic potential assessment along the faults in the eastern Tibet. Notably, the MW 6.8 Luding earthquake that ruptured the southern segment of the Xianshuihe Fault on 5 September 2022 supports the conclusions of this study.